Minahasan Vernacular House; Values, Meanings, And Forms - Ronald M P Kolibu; Agus Sachari; Pindi Setiawan (Mudra Jurnal Seni Budaya, 2020)
House is one of human’s three primary needs. It is developed alongside human civilization. Minahasa as a part of that civilization developed vernacular architecture based on their culture’s unique values, meanings, and forms. This article is a part of research concerned in answering the questions of (1) how are the knowledge and technology used by Minahasan to build their vernacular house, (2) how are the shape and form of Minahasan vernacular house in Minahasa’s cultural development, and (3) what are the value and meaning of Minahasan vernacular house for its people. These three questions were being addressed in this research by using qualitative method with ethnographic approach, where every steps and results will be described by interpretation of several patterns from the values, meanings, and forms found in the research process. Ethnography was utilized to see phenomena in this research. The results are identification of values, meaning, and forms development in Minahasan vernacular house.